1996
DOI: 10.1016/0021-9150(96)05924-2
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E polymorphism influences lipid phenotypic expression, but not the low density lipoprotein subfraction distribution in familial combined hyperlipidemia

Abstract: The impact of apo E polymorphism on interindividual variation in plasma lipid, lipoprotein concentrations, and LDL subfraction profiles was studied in 201 well-defined patients (88 men and 103 women) with familial combined hyperlipidemia (FCH). When corrected for the concomitant influences of age, gender and obesity, the allelic variation in the apo E gene was shown to explain a statistically significant portion of the variability in lipid and (apo)lipoprotein concentrations. Carriers of the apo e2 allele exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…36 However, so far only gene defects with a modifying, but not a major, effect on lipid and lipoprotein levels have been found in the lipoprotein lipase gene, 37,38 in the intestinal fatty acid-binding protein 2 gene, 39 and in the apoE gene. 40 In addition, the apoAI-CIII-AIV gene complex has been implicated in the etiology of FCHL, 41,42 but negative results have also been published. 43, 44 The locus in 1q21-q23 is a promising locus for FCHL 9 because the identical locus has FFA levels and the rates of oxidative and nonoxidative glucose disposal (meanϮSD) in control subjects and FCHL family members without FCHL, with hypercholesterolemia (type IIa dyslipidemia), with hypertriglyceridemia (type IV), and with combined hyperlipidemia (type IIb).…”
Section: Discussionmentioning
confidence: 99%
“…36 However, so far only gene defects with a modifying, but not a major, effect on lipid and lipoprotein levels have been found in the lipoprotein lipase gene, 37,38 in the intestinal fatty acid-binding protein 2 gene, 39 and in the apoE gene. 40 In addition, the apoAI-CIII-AIV gene complex has been implicated in the etiology of FCHL, 41,42 but negative results have also been published. 43, 44 The locus in 1q21-q23 is a promising locus for FCHL 9 because the identical locus has FFA levels and the rates of oxidative and nonoxidative glucose disposal (meanϮSD) in control subjects and FCHL family members without FCHL, with hypercholesterolemia (type IIa dyslipidemia), with hypertriglyceridemia (type IV), and with combined hyperlipidemia (type IIb).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in subjects of the San Antonio Heart Study, variations in apo E phenotype were associated not only with changes in the absolute LDL-cholesterol concentration, but also with changes in its composition [102]. However, in 201 affected FCH subjects of our families, these influences of apo E polymorphism on LDL heterogeneity were not observed [55]. In another study, the apo B100 EcoRI polymorphism, previously associated with variation in plasma lipids, was found to play a role in the susceptibility to the development of dense LDL in viscerally obese hyperinsulinaemic men [103].…”
Section: Genetic Aspects Of Ldl Heterogeneitymentioning
confidence: 60%
“…high for apo E3 and E4, but low for apo E2). A recent study on the effects of apo E polymorphism on presenting lipid phenotype in FCH suggested that differences in apo E isoform-related clearance may only contribute to the hyperlipidaemia as a result of other defects [55]. Further hydrolysis of triglycerides, predominantly by hepatic triglyceride lipoprotein lipase (HtgL), processes remaining IDL into LDL particles that then mainly consist of cholesteryl esters and apoprotein B100 [56].…”
Section: The Endogenous Pathwaymentioning
confidence: 99%
“…Based on the pathophysiology of FCH, several candidate genes have been evaluated, showing an association of FCH with lipoprotein lipase (LPL), 10 hepatic lipase (HL), 11 ApoAI/CIII/AIV 12 and ApoE. 13 Linkage analyses have been performed in several study populations to unravel the genetic defects causing FCH. Several regions of linkage have been identified, including a region on chromosome 1q21-23.…”
Section: Introductionmentioning
confidence: 99%